Paleoreef Maps: Evaluation of a comprehensive database of Phanerozoic reefs - Kießling, Wolfgang; et al. (Aapg Bulletin, 1999)
To get a better understanding of controls on reef development through time, we created a comprehensive database on Phanerozoic reefs. The database currently comprises 2470 reefs and contains information about geographic position/paleo-position, age, reef type, dimensions, environmental setting, paleontological and petrographical features, and reservoir quality of each buildup. Reef data were analyzed in two qualitatively different ways. The first type of analysis was by visualization of paleogeographic reef distribution maps. Five examples (Late Devonian, Early Permian, Late Triassic, Late Jurassic, middle Miocene) are presented to show the potential of paleoreef maps for paleogeographic and paleoclimatological reconstructions. The second type of analysis was a numerical processing of coded reef characteristics to realize major trends in reef evolution and properties of reef carbonates. The analysis of paleolatitudinal reef distributions through time shows pronounced asymmetries in some time slices, probably related to climatic asymmetries rather than controlled by plate tectonic evolution alone. The dominance of particular reef builders through time suggests that there are seven cycles of Phanerozoic reef development. First curves for the Phanerozoic distribution of bio-erosion in reefs, bathymetric setting, and debris potential of reefs are presented. The observed pattern in the temporal and spatial distribution of reefs with reservoir quality may assist in hydrocarbon exploration. Statistical tests on the dependencies of reefal reservoir quality suggest that large size, high debris potential, low paleolatitude, high amount of marine aragonite cement, and a platform/shelf edge setting favor reservoir quality. Reefal reservoirs are significantly enhanced in times of high evaporite sedimentation, elevated burial of organic carbon, low oceanic crust production, low atmospheric CO2 content, and cool paleoclimate, as well as when they are present in aragonite oceans.
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IGM.LP.paleor